Dostoevsky, Kierkegaard, Nietzsche and Kafka - Hubben, William, 1895-1974. (New York : Simon & Schuster, 1997)
Provides information about the lives and philosophies of the four nineteenth-century men and discusses how their writings foretold and influenced the social and political climate of the twentieth century.
"A Touchstone book.".
Adult
Keywords: Philosophy, Modern; Modern philosophy